Mechanisms of tachycardia on standing: studies in normal individuals and in chronic Chagas’ heart patients - NETO, J A MARIN; GALLO, L; MANCO, J C; RASSI, A; AMORIM, D S (Cardiovascular research, 1980)
The reflex tachycardia induced by change from the supine position to a 70° head-up tilt was studied in conscious normal individuals and in patients with chronic Chagas’ heart disease, known to constitute a model of parasympathetic denervation of the sinus node, in the absence of cardiac failure. Chagas’ patients showed markedly decreased heart rate responses during the initial 10 s following tilt to upright posture. A similar response was obtained in normals after parasympathetic blockade with atropine. β-adrenergic blockade failed to produce a significant effect on the initial heart rate response of normals, but heart rate increment, at 1 and 5 min of tilt, was significantly reduced in normals and abolished in patients. These results indicate a biphasic mode of tachycardia elicited by the upright posture: initially it depends on parasympathetic withdrawal, sympathetic stimulation becoming the predominant mechanism when stabilisation is attained in the orthostatic position.